PERSPEKTIF MAHASISWA TERKAIT KEMAMPUAN BERBICARA BAHASA ARAB DI LINGKUNGAN BERBAHASA ARAB - Ai Nani Femilasari; Muhamad Kholid Maulidi, Rizza Muqiedl Al-Khilafa, Shafa Setya Nabilah, Ahmad Fu'adin (CV. ADIBA AISHA AMIRA, 2024)
Arabic language learning in universities is now widespread, but there are still some problems, one of which is the lack of ability of students to speak Arabic. This problem is caused by not being accustomed to speaking Arabic in a language environment because the environment is not supportive. In order to overcome this problem, habituation, application and continuous practice by students are needed. Therefore, this study aims to determine the ability of students in speaking Arabic and the influence of the environment to improve the speaking ability. This research uses a qualitative method. This qualitative approach is used to explain and analyze individual phenomena, groups, events and perceptions. The source of this research was obtained by filling out questionnaires distributed offline to Arabic language students. The results of this research reveal some of the conditions that must be met in an effort to create a language environment, how influential the environment is in improving speaking skills using Arabic, and technological advances that can also have an impact on these skills.